Experimental study and thermodynamic analysis of coal spontaneous combustion characteristics. Issue 1 (2nd January 2023) - Zhang, Minbo; Wang, Zichao; Wang, LongKang; Zhang, Zhen; Zhang, Dangyu; Li, Chunxin
Abstract : Spontaneous coal combustion is one of the most common disasters in coal mine production. In order to explore the mechanism of coal spontaneous combustion more deeply, coal samples from the Yangdong wellfield of Jizhong Energy were selected for oxidative heat energy analysis experiments. A temperature-programmed experiment was selected to study the changes in characteristic parameters during the low-temperature oxidation of coal under different air supply conditions. TG-DSC experiments were conducted to study the characteristic temperature changes and thermodynamic characteristics of coal combustion processes at different heating rates. The study results show that the coal is most easily oxidised in the low-temperature oxidation stage when the air supply is 120 ml/min. The oxygen consumption rate, CO generation rate, and maximum and minimum heat release intensity are all greater at this airflow than under other conditions. The process of spontaneous combustion of coal has six characteristic temperature points and is divided into five stages. The characteristic temperature of the coal sample increased with the increase of the heating rate, and the TG/DTG curve showed a hysteresis phenomenon. DSC temperature curve shifts toward the high temperature with the increase of the heating rate, and the exothermic region is expanded. Isokinetic analysis (F-W-O and V-W) and Coats-Redfern model for calculating thermodynamic parameters. The activation energy of the samples decreased with the increase of the heating rate in the range of 2∼20°C·min −1 and showed a decreasing trend with the increase of the conversion rate.